Liberalization and territorial advantages: Analysis of the manufacturing sector in Mexico - Verduzco, Gustavo Félix (Estudios Económicos de El Colegio de México, 2005)
This paper is a theoretical and empirical work about trade liberalization and regional changes of the manufacturing industry in Mexico. Diverse studies argue that the closed economy induced a concentrated pattern and that the trade opening represents opposite forces that favor the regional transfer towards northern. This study agrees with the first part of the proposal, nevertheless, argues that elements exist such as economies of agglomeration, vertical linkages, and other advantages of territories that can compensate the proximity with North America. The theoretical analysis is based on the “new economic geography” and the empirical one in an econometric model.